Optimization on the formulation of sizing to enhance the mechanical properties of basalt fiber. Issue 4 (3rd April 2021) - Xing, Dan; Xi, Xiong-Yu; Qi, Ming-Gang; Zheng, Qing-Bin; Ma, Peng-Cheng
Abstract: Sizing, a liquid mixture consisting of film former, coupling agent, antistatic and lubricant agents, is normally applied onto the surface of basalt fiber (BF) immediately after the filament was drawn from the melt. In this article, the effect of concentration of constituents in sizing on the mechanical properties of BF was investigated using a Taguchi method with orthogonal array design. The results showed that the Taguchi method is an effective way to formulate the sizing for BF, and there was a good agreement between wettability of sizing and enhancement to mechanical properties of BF. The concentration of main film former in sizing exhibited the strongest effect on governing the tensile strength of BF, followed by the concentrations of auxiliary film former and coupling agent. In addition, the chemical and physical interactions among the components in sizing should be considered when designing a suitable formula of sizing for BF.